America’s most wanted criminals: comparing cybercriminals and traditional criminals - Payne, Brian (Criminal justice studies, 2019)
Reports of cybercrime have escalated over the past decade. While these crimes have increased, our understanding about the dynamics surrounding cyber offenders has not kept pace. Few studies have considered the characteristics of serious cyber criminals in comparison to other types of criminals. To fill this void in the literature, we examine a sample of cybercriminals appearing on the FBIs Most Wanted List and compare the characteristics of these offenders to other most wanted offenders. Results suggest that the most wanted cyber offenders are similar to other offenders in that it is a male-dominated offense category, but they are different from other offenders in that they are younger and more likely to exhibit certain types of physical and lifestyle characteristics. Implications for policy and future research are provided.